Early-Career Teachers’ Self-Reported Challenges in Implementing Content and Language Integrated Learning in Indonesian Elementary Schools - Risa Fitria; Ika Kana Trisnawati; Ryan Besa Estillomo; Disa Evawani Lestari (Pedagogy Review, 2026)
Content and Language Integrated Learning (CLIL) is a pedagogical approach that aims to increase students’ subject knowledge and English proficiency simultaneously through meaningful classroom interaction. However, despite its increasing popularity in Indonesia, early-career teachers frequently encounter linguistic and pedagogical challenges that affect the quality of CLIL teaching. This study explored the self-reported experiences of 19 early-career teachers in applying CLIL in Indonesian elementary schools. All participants had completed a Medium of Instruction (EMI) elementary teacher education program at a private university in Indonesia, which provides a unique context to study how prior English exposure influences classroom practices. Data were collected using an open-ended questionnaire and were analyzed thematically with a descriptive qualitative approach. The findings suggest that although participants had adequate general English language skills and were confident in daily communication, they still struggled to use subject-specific academic vocabulary and to cope with English-language classroom instructional discourse. The teachers also found it difficult to deal with students with varying levels of English proficiency. Therefore, they used adaptive strategies, such as repetition, reformulation, and first-language (L1) use, to maintain classroom interaction and students' understanding. These findings suggest that successful CLIL implementation depends not only on general English proficiency but also on teachers’ ability to use disciplinary teaching discourse and to flexibly adapt their language to meet students’ needs. The study concludes that pre-service teacher education should go beyond developing general English fluency and provide explicit preparation in CLIL-oriented classroom discourse, subject-specific academic language, and adaptive pedagogical strategies. These findings illuminate the linguistic and pedagogical preparation that is needed by early-career teachers in CLIL classrooms and have implications for the design of teacher education programs in similar EMI and bilingual contexts. Keywords: Content-Language Integrated Learning (CLIL), Early-career Elementary Teachers, Disciplinary Academic Language, English-Medium Instruction, Teacher Preparation